The “Ten-percent Brain Myth” guided with the Fundamentals of Jaina’s Theory of Knowledge. - Arora, Megha (International Journal of Psychosocial Rehabilitation, 2020)
Great religions to pragmatic capacities sporadically abound in the stories of supernatural phenomena which subsumes telepathy, clairvoyance and precognition. However, unfortunately treated as the topics of spiritualism, witchcraft and edification, not the materials of Scientific Enquiry. Whatsoever, have been deciphered about these queer speculations, the most prevalent sole concept is : namely, that there can be sense-experiences from the realm which is not accessible to human brain and sense organs. Possessor of these senses which are not currently accessible to average humans can be a omniscient being tapping to his full potential. Presently, we have no language or any communication system to describe them intelligibly. When inquiring about these affairs we cannot avoid absurdity as presently we lack any linguistic convention on it. Our linguistic convention is derived from the physical world in which the supernatural is not considered as "Normal". It is considerably strained with "Abnormality" in the first place. My aim in this paper is to reconcile this Orthodox Psychology with Science and Philosophy which certainly appears conflicting. This inquiry leads me to enable the 10 percent brain myth.